Effect of parity on back fat thickness, body condition score and milk yield in Jersey crossbred cows of lower Gangetic region - Paul, Abhishek; Bhakat, Champak; Mondal, Santu (Indian Journal of Dairy Science, 2022)
The present experiment was carried out to know the effect of parities on body score, back fat thickness and milk yield of Jersey crossbred cows. A total of 43 crossbred jersey cattle were examined for 120 days postpartum and divided into four groups, based on their parity number. Correlation and relationship study has revealed significant effect of parity on various parameters. The overall correlation coefficient between BCS and BFT were found to be 54%, 92%, 94% and 90% for P1, P2, P3 and P4 respectively. However, positive to negative significant correlation between BFT and milk yield by parity 1,2,3,4 were 46%, 26%, -10% and -12% respectively. Increased BCS at calving was associated with greater MY in first and second parity cows, and reduced MY in cows of third parity or greater. Furthermore, the correlation coefficient between BFT and BW were found to be low in P1 (r=0.58) and high in P4 (r=0.78). The changes in body fat thickness (BFT) and body weight (BW) by parity difference were most distinct in younger cows i.e. -47.92 percent and -12.05 percent respectively. Relationship (RÂ²) between BFT and BCS in different parity group were 0.29, 0.87, 0.85 and 0.83 respectively (p